Chronic Obstructive Pulmonary Disease with Incidence of Heart Failure and Its Influencing Factors - Andry Wahyudi Agus; Adrianison Adrianison; Faisal Yunus; Zahtamal Zahtamal; Dyah Siswanti Estiningsih (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: Chronic obstructive pulmonary disease (COPD) is often associated with cardiovascular disease because it has the same risk factors as smoking. One of the cardiovascular complications in COPD is heart failure. Echocardiography examination is a tool to evaluate changes of the heart both anatomically and functionally. This study aimed to determine the relationship between COPD and heart failure by echocardiography examination in stable COPD patients.Methods: This was a descriptive-analytic study using a cross-sectional design for COPD patients who visited the Lung Polyclinic of Arifin Achmad Hospital, Pekanbaru, Riau, which was conducted from November 2020 to March 2021. Subjects who met the inclusion criteria were examined by spirometry, chest X-rays, and echocardiography.Results: In this study, there were 66 stable COPD subjects. It was found that 15.2% of subjects had right heart failure based on the tricuspid annular plain systolic excursion (TAPSE) assessment and 7.6% of the subjects had left heart failure based on the left ventricular ejection fraction (LVEF) value. Right ventricular dilatation (p = 0.000), right ventricular dysfunction (p = 0.005), and increased probability of pulmonary hypertension (PH) (p = 0.000) were significantly associated with a decrease in the first second forced expiratory volume (FEV1).Conclusion: The severity of COPD with FEV1 <50% had a significant relationship with dilatation, dysfunction of right ventricular, and increased the probability of incidence of PH based on parameters tricuspid regurgitation (TR). A history of exacerbations ≥2 times in a year caused right ventricular dilatation, decreased right ventricular function, and increased the probability of PH.